TECHNOLOGICAL AND METHODOLOGICAL FOUNDATIONS FOR DEVELOPING DIGITAL COMPETENCIES IN PRE-SERVICE TEACHERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article identifies the technological and methodological aspects of developing digital-creative competencies among pre-service teachers in the context of distance education in the Republic of Uzbekistan. It also clarifies the essence of key concepts such as “competence,” “digital competence,” “digital-technological competence,” “digital-methodological competence,” “creativity,” and “digital pedagogical campus”. During the research process, an online questionnaire and an online test were conducted. A mobile application was developed for the implementation of the online test. Only Uzbek pre-service teachers participated in the experimental study, and their digital competencies were compared with those of Russian pre-service teachers. The article defines the content of digital-technological and digital-methodological competencies of pre-service teachers in distance learning conditions. In addition, it presents the structure and development framework of interrelated competencies of future teachers in the context of distance education.